Cloud, Edge, and Fog Computing and Security for the Internet of Things - Al-Alshaqi, Mohammed; B. Rawat, Danda (EAI Endorsed Transactions on Internet of Things, 2020)
In this paper, a method is purposed that detects the masquerade activity of cloud data. In this method, the combination of the decoy technique and the user’s behaviour profile technique are used to improve the security of data in the cloud. This research has the main focus on understanding the use of these computing paradigms with the internet of things. The security concerns and its possible solutions are described. Therefore, the comparative analysis is conducted, which elaborates on each paradigm in the internet of things. The future consent of cloud, edge, and fog computing is also directed, which gives the innovative vision for the data handling with the internet of things.
Keywords: Security for the internet of things (IoT); Cloud Computing; Edge computing; Fog computing with the internet of things (IoT)